Vietnam Solar Competitive Bidding Strategy and Framework - World Bank (World Bank, Washington, DC, 2020)
Solar power generation is an increasingly attractive option for Vietnam thanks to recent cost reductions, fast construction timelines, and the contribution solar power can make to ensuring energy security and environmental sustainability. Aiming to scale up solar generation in a sustainable and affordable manner, the Government of Vietnam plans to shift from the feed-in-tariff (FIT) to a competitive bidding mechanism. With the support of the World Bank, the Government of Vietnam is designing the program based on the present strategy developed with input from several ministries, the private sector, and development partners. The strategy presents recommendations to the Government of Vietnam aiming to provide a clear path to develop a sustainable solar program. As part of a carefully designed strategy, decisions must be made in the following areas: (i) the roles and responsibilities of the various public and private parties, (ii) whether changes need to be made to the existing laws and regulations, (iii) the types of deployment schemes that are best suited to Vietnam’s circumstances, and (iv) what risks the Government of Vietnam will internalize and what mitigation instruments it might offer IPPs. The clarification of these points prior to the selection of an IPP will help speed up the IPP selection process, reduce the chances of procurement failure, and provide a long-term vision for deploying solar projects. From the independent power Producers’ (IPPs) perspective, a clear government strategy reduces perceived risks related to a weak or inadequate legal framework, unclear selection process, or other development concerns.